Degradasi Masker Sekali Pakai dengan Vermiremediasi dan Penambahan Isolat Bakteri Teluk Lampung - Deviany, Deviany; Achmad, Feerzet; Rosafira, Adela; Aini, Syarifah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The use of disposable face masks during the Covid-19 pandemic has resulted in the emergence of mask waste polluting aquatic environments due to poor management. This waste will decompose into microfibers which accumulate in aquatic organisms. The combination of vermiremediation with the addition of degrading microorganisms can be one of the solutions for treating disposable mask waste. In this study, Eudrilus eugeniae, an earthworm species, was used in vermiremediation with variations in the treatment by adding indigenous bacterial isolate from the waters of Lampung Bay which has been proven able to degrade disposable masks. The results showed that the vermiremediation technique can be used to degrade disposable masks, indicated by a decrease in mask weight after incubation for two months in the amount of 0.03 grams and 0.05 grams for the treatment with the Eudrilus eugeniae and a combination of bacterial isolate respectively against the initial weight. Lampung Bay indigenous bacterial isolate helped accelerate the mask degradation process in the combined vermiremediation technique. The carbon, nitrogen, phosphorus, and potassium contents of the compost produced by the vermiremediation process have met the SNI for compost from domestic organic waste.